A Comparative Analysis of the Doctrinal Consequences of Interpretive Disagreement for Implied Constitutional Rights - Zoë Robinson (Washington University Global Studies Law Review, 2012)
This Article addresses a fundamental and unexamined issue in the debate over implied constitutional rights: the effect that interpretive disagreement has on the development of implied rights more generally. Taking a comparative approach, the Article examines the implied right to abortion in the United States and the implied right to the freedom of political communication in Australia. The Article argues that despite the acceptance of both rights over time, the doubts concerning the initial recognition of the rights as well as the interrelated problems of judicial self-consciousness regarding the vulnerability of the implied right in the face of continuing controversy and the paucity of interpretive resources with which doctrinal developments could be supported, have adversely affected their development. Tracing the effects of disagreement on the development of two moderately secure implied rights across two jurisdictions, this Article ultimately concludes that the stunted development of implied rights in both jurisdictions indicates that implication is an especially weak form of rights protection in constitutional democracies.
Keywords: Comparative law; Australia; United States; Constitutional rights; Implied rights